I minori della post-modernità di fronte alla responsabilità penale: questioni di maturità e di (neuro)scienza - Bertolino, Marta (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
Public attention is periodically called to discuss the issue of criminal liability age to legitimize some legislative choices aiming at lower the limit below the fourteen years old, as currently provided for by the Rocco Code of the 1930 (artt. 97 and 98). However, the majority and most authoritative criminal doctrine is not in favor of lowering the criminal liability age. On the one hand, it would not be justified by recent criminal studies taking into account the most up-to-date scientific evidence, as particularly provided by neurosciences, which deny any necessity of putting earlier criminal liability age in the current reality; on the other, the statistical data do not seem to show any worsening of juvenile crime. The multi-level and interdisciplinary debate about capacity of ‘young criminals’ and majority as to criminal liability represents a crucial problem, wherein the contribution of neurosciences is important, since it is useful to understand the significance of ‘majority’ and to determine the threshold to be considered as relevant with reference to criminal liability.